2002
DOI: 10.1890/0012-9658(2002)083[3048:teeaes]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Edge Effect and Ecotonal Species: Bird Communities Across a Natural Edge in Southeastern Australia

Abstract: Ecotones have been considered as unique environments, and the concepts of edge effect and ecotonal species have been widely used, especially in avian community ecology. We studied the patterns of bird densities across heath-wood edges at replicated sites in three locations in southeastern Australia. Multivariate analysis showed that the bird community in the ecotone was intermediate between the heath and wood communities, indicating that the ecotone contained a mixing of species rather than a unique bird commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 27 publications
5
52
2
2
Order By: Relevance
“…The predominantly neutral or delayed responses of birds to forest edges reported in previous studies indicate a high variability of edge effects according to the biogeographic or regional landscape contexts (Baker et al, 2002;Laurance et al, 2007). Here, we found additional effects of landscape diversity on bird functional diversity, but not on avian insectivory, which was only significantly affected by edge effects.…”
Section: Landscape-scale Heterogeneity and Bird Functional Diversitysupporting
confidence: 65%
See 1 more Smart Citation
“…The predominantly neutral or delayed responses of birds to forest edges reported in previous studies indicate a high variability of edge effects according to the biogeographic or regional landscape contexts (Baker et al, 2002;Laurance et al, 2007). Here, we found additional effects of landscape diversity on bird functional diversity, but not on avian insectivory, which was only significantly affected by edge effects.…”
Section: Landscape-scale Heterogeneity and Bird Functional Diversitysupporting
confidence: 65%
“…For each of the 24 forest stands, we paired an edge and an interior plot located at 50 m from the edge (N = 24 9 2 = 48 plots). This distance was chosen according to previous studies that had demonstrated that 50 m was a recurrent threshold of approximate edge influence for forest vegetation and birds (Baker et al, 2002;Harper et al, 2005;Rodewald & Vitz, 2005). The use of 50 m distance allowed us to include small forest fragments in the experiment as well as larger stands to study a complete gradient of forest fragment size.…”
Section: Bird Community Samplingmentioning
confidence: 99%
“…Proximity to edge habitats has been found to play a key role in structuring bird communities (e.g., Flaspohler et al 2001, Baker et al 2002. Distance-to-edge and variables reflecting edge density did enter into some of our analyses, but explained relatively small amounts of variation.…”
Section: Discussionmentioning
confidence: 93%
“…Immediately after fire, structural and floristic differences between burnt and unburnt patches are pronounced, and are likely to decrease with TSF as burnt vegetation regenerates. Although edge effects can be negative for forest passerines (Baker et al 2002, Barbaro et al 2012, it is plausible that a complex configuration of burnt and unburnt patches enhances functional diversity because the edge zone provides unique resources (Law and Dickman 1998).…”
Section: Responses Of Functional Diversity To Tsfmentioning
confidence: 99%